2020
DOI: 10.1007/s10803-020-04452-0
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Multisensory Integration and the Temporal Binding Window in Autism Spectrum Disorder

Abstract: The present study examined the relationship between multisensory integration and the temporal binding window (TBW) for multisensory processing in adults with Autism spectrum disorder (ASD). The ASD group was less likely than the typically developing group to perceive an illusory flash induced by multisensory integration during a sound-induced flash illusion (SIFI) task. Although both groups showed comparable TBWs during the multisensory temporal order judgment task, correlation analyses and Bayes factors provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Similarly, we found that the stronger the ASD characteristics in the general population, the higher the temporal resolution and the lower the likelihood that MSI will occur (18). We also conducted the same experiment in individuals with highfunctioning ASD and reported a similar trend (19), which suggested that MSI is affected by more fundamental information processing characteristics. Therefore, interventions targeting lower-order functions may also improve higher-order functions.…”
Section: Behavioral Mechanisms Underlying Atypical Msi In Asdsupporting
confidence: 55%
See 2 more Smart Citations
“…Similarly, we found that the stronger the ASD characteristics in the general population, the higher the temporal resolution and the lower the likelihood that MSI will occur (18). We also conducted the same experiment in individuals with highfunctioning ASD and reported a similar trend (19), which suggested that MSI is affected by more fundamental information processing characteristics. Therefore, interventions targeting lower-order functions may also improve higher-order functions.…”
Section: Behavioral Mechanisms Underlying Atypical Msi In Asdsupporting
confidence: 55%
“…Some have reported that people with ASD and TD show equal susceptibility to the SIFI task (8,16,17). In contrast, others have shown that individuals with ASD have reduced (14,19) or enhanced (15) susceptibility to the SIFI task. Such inconsistencies may be attributed to a developmental delay rather than a persistent difference (23).…”
Section: Characteristics Of Multisensory Processing In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unclear whether a smaller audiovisual TBW would benefit or impair perceptual processing. For example, several studies have found that people having a smaller TBW showed decreased multisensory integration (e.g., reduced susceptibility for sound-induced flash illusion; Kawakami, Uono, Otsuka, Yoshimura, et al, 2020; Kawakami, Uono, Otsuka, Zhao, & Toichi, 2020) because integration could occur only within a narrower time window for them. Moreover, in healthy individuals, a narrower TBW was associated with more self-reported autistic traits, including both social difficulties (Kawakami, Uono, Otsuka, Zhao, & Toichi, 2020; Yaguchi & Hidaka, 2018) and attention to detail (van Laarhoven et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For both visual and auditory processing, temporal coherence across assemblies of neurons that code for different stimulus features is thought to promote binding of those features into coherent perceptual objects [3,4]. A leading hypothesis about sensory processing abnormalities in autism spectrum disorder (ASD) is that this kind of temporal "synthesis" of sensory information is atypical [5][6][7][8]. This hypothesis stems from behavioral data indicating that individuals with ASD often show impaired processing of dynamic stimuli, such as the coherent motion of visual dots [9].…”
Section: Introductionmentioning
confidence: 99%